2014
DOI: 10.1152/ajprenal.00664.2013
|View full text |Cite
|
Sign up to set email alerts
|

Renal vasoconstriction by vasopressin V1a receptors is modulated by nitric oxide, prostanoids, and superoxide but not the ADP ribosyl cyclase CD38

Abstract: Renal blood flow (RBF) responses to arginine vasopressin (AVP) were tested in anesthetized wild-type (WT) and CD38(-/-) mice that lack the major calcium-mobilizing second messenger cyclic ADP ribose. AVP (3-25 ng) injected intravenously produced dose-dependent decreases in RBF, reaching a maximum of 25 ± 2% below basal RBF in WT and 27 ± 2% in CD38(-/-) mice with 25 ng of AVP. Renal vascular resistance (RVR) increased 75 ± 6% and 78 ± 6% in WT and CD38(-/-) mice. Inhibition of nitric oxide (NO) synthase with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 95 publications
0
6
0
1
Order By: Relevance
“…Animal studies have demonstrated that O 2 Ϫ dismutation by tempol attenuates renal vasoconstriction induced by ANG II, AVP, endothelin, and norepinephrine, and that this vasoconstrictor action of O 2 Ϫ may involve quenching of NO and also an action independent of NO (39,40,65). On the other hand, our laboratory (65) has shown previously that O 2 Ϫ enhances the renal vasoconstrictor action of AVP primarily by limiting the bioavailability of NO, suggesting different roles as a function of stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that O 2 Ϫ dismutation by tempol attenuates renal vasoconstriction induced by ANG II, AVP, endothelin, and norepinephrine, and that this vasoconstrictor action of O 2 Ϫ may involve quenching of NO and also an action independent of NO (39,40,65). On the other hand, our laboratory (65) has shown previously that O 2 Ϫ enhances the renal vasoconstrictor action of AVP primarily by limiting the bioavailability of NO, suggesting different roles as a function of stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, NO production affects the myogenic mechanism, as discussed in section VIC. Moreover, activation of MD cells can accelerate the rate of relaxation associated with the generation of PGE 2 (218, 1036,1334) and NO (298, 1036). Indeed, Loutzenhiser et al demonstrated later that adding exogenous NO or cGMP to the HNK preparation to more closely simulate the in vivo paracrine modulation, preferentially reduced the delay in the vasodilation response to a reduced RPP (R. Loutzenhiser, personal communication), thereby reducing the time difference between myogenic relaxation and constriction which more closely approximated to those observed in vivo.…”
Section: Kinetics Of the Myogenic Responsementioning
confidence: 99%
“…V2 receptors buffer the vasoconstrictor effects of vasopressin in the kidney, however, their expression and action vary among species. [40][41][42] Although cortical arteries and VR seem to constrict to vasopressin, its effect on glomerular arterioles is weak or undetectable. 43,44 Reduced medullary blood flow due to VR constriction decreases interstitial fluid pressure and sodium excretion thereby affecting blood pressure.…”
Section: Effect Of Acute Hyperglycemia On Renal Microvesselsmentioning
confidence: 99%